Paediatric Horner's syndrome: is investigation for underlying malignancy always required?. Issue 10 (October 2019) - Braungart, Sarah; Craigie, Ross J; Farrelly, Paul; Losty, Paul Damian
Abstract : Objective: Horner's syndrome (HS) is characterised by a triad of ocular miosis, ptosis and anhidrosis. HS may be a subtle sign of occult pathology in otherwise asymptomatic children, neuroblastoma (NBL) being the the most common associated malignant tumour. Despite such knowledge, the incidence of underlying malignancy in children with HS remains unclear and robust evidence to guide best clinical practice is sparse. We performed a systematic review of the literature with the aim of identifying the incidence of NBL in children with HS of unknown aetiology, and establishing if screening for NBL should be routinely performed in this patient population. Methods: Systematic review of the literature (PubMed and Ovid/Medline database, 1961–2018). Results: The initial search identified 334 manuscripts, of which 8 studies were included in the final analysis. All reports were single-centre retrospective studies without control groups and included a total of 152 patients (age range 0–20 years). All studies investigated patients with HS but without previously established diagnosis. In the studies included, 17 out of a total of 152 patients were diagnosed with a space-occupying lesion. 12 out of the 152 patients were subsequently detected with NBL. Conclusion: HS in children may be the first sign of occult malignancy. We report the first systematic review that comprehensively investigates the incidence of malignancy in this unique patient cohort. We show that HS of unknown aetiology in children warrants further investigation(s) to exclude an underlying space-occupying lesion. This should include cross-sectional imaging of the brain, neck and thorax, plus urinary catecholamines for prompt diagnosis and treatment.